Association of Consanguineous Marriage with Sociodemographic Characteristics of Parents and its Impact on Mortality and Morbidity in off Springs: Analytical Study from Punjab, Pakistan - Tariq, Naseer Alam; Saeed Awan, Bushra Ameer; Bajwa, Ali Hassan; Amin, Areesha; Zahid, Maryam; Ahmed, Haseeb; Mujahid, Usama (Pakistan Armed Forces Medical Journal, 2024)
Objective: This study aims to fill the gap in literature by demonstrating the significance of Sociodemographic determinants and its impact on mortality and morbidity in off springs of consanguineous couples in Punjab, Pakistan.Study Design: Cross-sectional analytical study.Place and Duration of Study: Study was four months from Nov 2021 to Mar 2022, online on married couples in Punjab, Pakistan.Methodology: Married couples of both the consanguineous and non-consanguineous marriages who were able to participate and understand questions in survey were included. Sample size of 338 was calculated using Open epi info software. Keeping in view the response rate of 76% forms were distributed to 400 participants. Sampling technique uses was non probability purposive sampling. The questionnaire included Sociodemographic information and questions related to morbidity and mortality in off springs for qualitative variables, relevant frequencies and percentages were determined. Chi square test was applied to determine relationship between two qualitative variables, a p-value of 0.05 was considered statistically significant.Results: Total n=193(64%) were non-consanguineous couples, while n=107(36%) were consanguineous. Majority were between 46-60 years of age and monthly income of Rs. 71,000-90,000 Almost one third was graduates=91(30%) and post graduates n=84(28%).The prevalence of diseases came high in children of consanguineous families n=13(4%) as compare to non-consanguineous. There was a significant association between type of marriage disease (p=0.001) and under-five mortality in children (p=0.003). Conclusion: The children born to consanguineous couples exhibited more burden of inherited disorders than children born to non-consanguineous couples.